The Effectiveness of the MBKM-Aligned Research-Based Learning Model in Enhancing Students’ Problem-Solving Skills - Nasution, Aida Rahmi; Ratnawati, Ratnawati; Meldina, Tika; Yonita, Wezi (Jurnal Tarbiyatuna, 2025)
This study investigates the effectiveness of the MBKM-based Research-Based Learning (RBL) model in enhancing students’ problem-solving skills in Madrasah Ibtidaiyah (MI) science instruction. The RBL model engages students in research-oriented activities to foster critical, analytical, collaborative, and innovative thinking. The study involved 58 students from the PGMI Study Program using a quantitative quasi-experimental design with a nonequivalent control group. One experimental and one control class were used, with data collected through observation, tests, and documentation. The objectives were to assess: (1) students’ problem-solving abilities prior to the implementation of the RBL model, and (2) the model’s effectiveness following its application. Data analysis included validity and reliability checks, tests of normality and homogeneity, and hypothesis testing using one-way ANOVA. Prior to the intervention, average problem-solving scores were comparable between the experimental (44.14) and control groups (44.83), indicating baseline equivalence. After implementing the RBL model, one-way ANOVA results showed a significant improvement in the experimental group’s problem-solving skills (F = 55.238, p < 0.001), indicating a positive effect of the intervention. Despite its promising results, the study is limited by its small sample size, short duration, and specific focus on MI science content within the PGMI program, which may limit broader generalizability. Nonetheless, the findings support the effectiveness of the MBKM-aligned RBL model in improving students’ problem-solving skills.